2017
DOI: 10.18632/oncotarget.23257
|View full text |Cite
|
Sign up to set email alerts
|

Impact of prenatal cold stress on placental physiology, inflammatory response, and apoptosis in rats

Abstract: Prenatal cold stress is one of the earliest factors affecting mammalian health, and is associated with neonatal growth retardation and immune dysfunction, thus increasing disease susceptibility. The mechanisms underlying these observations remain unclear; hence, the objective of this study was to elucidate placental responses to cold stress. 60 maternal rats were randomly allocated to either stressed (n = 30) or non-stressed (control, n = 30) treatment conditions and 30 pubs (n=15) were used for the pups analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 50 publications
1
19
0
Order By: Relevance
“…In rodents, studies have shown that maternal stress during pregnancy is associated with an increase in pro-inflammatory cytokines such as IL-1β and IL-6 in the placenta [36,77,78]. Cold stress in pregnant rats resulted in an increase in IL-1β in the labyrinth [78]. In this study, placental samples per dam were of mixed sex, and accordingly conclusions about sex-specific effects were precluded.…”
Section: Effect Of Maternal Gestational Stress On Inflammationmentioning
confidence: 80%
See 1 more Smart Citation
“…In rodents, studies have shown that maternal stress during pregnancy is associated with an increase in pro-inflammatory cytokines such as IL-1β and IL-6 in the placenta [36,77,78]. Cold stress in pregnant rats resulted in an increase in IL-1β in the labyrinth [78]. In this study, placental samples per dam were of mixed sex, and accordingly conclusions about sex-specific effects were precluded.…”
Section: Effect Of Maternal Gestational Stress On Inflammationmentioning
confidence: 80%
“…The strong association between stress and inflammation has led to an increased interest in examining inflammatory markers in the intrauterine environment both in rodents and in humans. In rodents, studies have shown that maternal stress during pregnancy is associated with an increase in pro-inflammatory cytokines such as IL-1β and IL-6 in the placenta [36,77,78]. Cold stress in pregnant rats resulted in an increase in IL-1β in the labyrinth [78].…”
Section: Effect Of Maternal Gestational Stress On Inflammationmentioning
confidence: 99%
“…This is physiologically plausible based on evidence showing that extreme temperature (heat or cold stress) predisposed placenta at a higher risk of inflammation triggered by air pollutants. 51 , 52 …”
Section: Discussionmentioning
confidence: 99%
“…However, research using rodent models suggests that prenatal cold stress can modulate the maternal hypothalamus-pituitary-adrenocortical (HPA) activity [ 40 ] responsible for releasing glucocorticoids, including cortisol, as well as altering maternal metabolism [ 41 ]. Interestingly, maternal cold stress can affect placental physiology [ 42 ]; therefore, it is conceivable that temperature is likely to affect intestinal development, similar to other maternal stressors such as undernutrition [ 43 ].…”
Section: Introductionmentioning
confidence: 99%